Removing outliers from the normative database improves regional atrophy detection in single-subject voxel-based morphometry - Schultz, Vivian; Hedderich, Dennis M.; Schmitz-Koep, Benita; Schinz, David; Zimmer, Claus; Yakushev, Igor; Apostolova, Ivayla; Özden, Cansu; Opfer, Roland; Buchert, Ralph (Neuroradiology, 2024)
Purpose Single-subject voxel-based morphometry (VBM) compares an individual T1-weighted MRI to a sample of normal MRI in a normative database (NDB) to detect regional atrophy. Outliers in the NDB might result in reduced sensitivity of VBM. The primary aim of the current study was to propose a method for outlier removal (“NDB cleaning”) and to test its impact on the performance of VBM for detection of Alzheimer’s disease (AD) and frontotemporal lobar degeneration (FTLD). Methods T1-weighted MRI of 81 patients with biomarker-confirmed AD ( n = 51) or FTLD ( n = 30) and 37 healthy subjects with simultaneous FDG-PET/MRI were included as test dataset. Two different NDBs were used: a scanner-specific NDB (37 healthy controls from the test dataset) and a non-scanner-specific NDB comprising 164 normal T1-weighted MRI from 164 different MRI scanners. Three different quality metrics based on leave-one-out testing of the scans in the NDB were implemented. A scan was removed if it was an outlier with respect to one or more quality metrics. VBM maps generated with and without NDB cleaning were assessed visually for the presence of AD or FTLD. Results Specificity of visual interpretation of the VBM maps for detection of AD or FTLD was 100% in all settings. Sensitivity was increased by NDB cleaning with both NDBs. The effect was statistically significant for the multiple-scanner NDB (from 0.47 [95%-CI 0.36–0.58] to 0.61 [0.49–0.71]). Conclusion NDB cleaning has the potential to improve the sensitivity of VBM for the detection of AD or FTLD without increasing the risk of false positive findings.